(3GdVHW GdEOGQi SdWGfg hMOhOg ai OhdI bWQ (B/ s - (3YjSi Hf SYO GdfYjei s; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQI s (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2009)
(3dbO JfGhdJ GdQSGdI (B" (3GdVHW GdEOGQi SdWGJg hMOhOg ai OhdI bWQ (B" (3OQGSI ebGQfI eY GdfXGe GdbGfhfi ai cd ef aQfSG heUQ hJe JbSje GdQSGdI Edi GdJWhQ GdJGQjNi ddVHW GdEOGQi ai OhdI bWQ hHjGf eaghe GdVHW GdEOGQi hWHjYJg hZGjGJg (B. (3hbO JfGhd GdHMK SdWGJ GdVHW GdEOGQi hYQV dgFGJ GdVHW GdEOGQi hHjGf CYeGd GdVHW GdEOGQi YQV GdHMK GjVG HYV GdJWHjbGJ GdYedjI dCYeGd GdVHW GdEOGQi (B. (3hJfGhdJ GdOQGSI MOhO GdVHW GdEOGQi ef NdGd GdMOhO GdOSJhQjI hGdbGfhfjI GdebjOI dSdWI GdVHW GdEOGQi hMOhO GdELQGA GdVGHW s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2009s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdMOhO GdOSJhQjI hGdbGfhfjI s; (3SdWGJ GdVHWs; (3bjhO GdGLQGA GdVGHW s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQI s -- (3cdjI GdMbhbs